The reversible impairment of behavioral variant frontotemporal brain sagging syndrome: Challenges and opportunities - Wouter I. Schievink; Marcel Maya; Zachary Barnard; Rachelle B. Taché; Ravi S. Prasad; Vikram S. Wadhwa; Franklin G. Moser; Miriam Nuño (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Due to loss of brain buoyancy, spontaneous spinal cerebrospinal fluid (CSF) leaks cause orthostatic headaches but also can cause symptoms indistinguishable from behavioral variant frontotemporal dementia (bvFTD) due to severe brain sagging (including the frontal and temporal lobes), as visualized on brain magnetic resonance imaging. However, the detection of these CSF leaks may require specialized spinal imaging techniques, such as digital subtraction myelography (DSM). Methods We performed DSM in the lateral decubitus position under general anesthesia in 21 consecutive patients with frontotemporal dementia brain sagging syndrome (4 women and 17 men; mean age 56.2 years [range: 31–70 years]). Results Nine patients (42.8%) were found to have a CSF‐venous fistula, a recently discovered type of CSF leak that cannot be detected on conventional spinal imaging. All nine patients underwent uneventful surgical ligation of the fistula. Complete or near‐complete and sustained resolution of bvFTD symptoms was obtained by all nine patients, accompanied by reversal of brain sagging, but in only three (25.0%) of the twelve patients in whom no CSF‐venous fistula could be detected (P = 0.0011), and who were treated with non‐targeted therapies. Discussion Concerns about a spinal CSF leak should not be dismissed in patients with frontotemporal brain sagging syndrome, even when conventional spinal imaging is normal. However, even with this specialized imaging the source of the loss of spinal CSF remains elusive in more than half of patients.